ORIGINS OF PARTY ALIGNMENT IN ENGLAND - EMPIRICAL STUDY OF VICTORIAN ELECTIONS - Pyykönen, Vinski (My University, 2025)
In this study we empirically examine the development of party oriented electorate in 19th century England by utilizing a set of recently digitized voting records, known as poll books. Poll books provide us with unique individual-level data on voting behavior that allows us to avoid the pitfalls of making inferences using aggregated data. We use a difference-in- difference setup to study voting behavior between working and middle class voters. We observe a statistically significant drop in levels of split voting, and increase in liberal candi- date’s vote shares, in 1865 general election and following elections. This reduction in split voting and increased amount of votes for liberal candidates is significantly stronger among the working class voters. Our results provide new evidence for the claim that in England the electorate became party oriented before the major expansion of the franchise, Second Reform Act of 1867.
Keywords: party alignment, differences-in-differences, poll books, voting